2015
DOI: 10.1111/jgh.13044
|View full text |Cite
|
Sign up to set email alerts
|

Fetal and infant exposure to the Chinese famine increases the risk of fatty liver disease in Chongqing, China

Abstract: Exposure to the Chinese famine during fetal life and infancy was associated with an increased risk of fatty liver disease in adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 32 publications
4
18
0
Order By: Relevance
“…Our previous study found that exposure to China's Great Famine of 1959–1962 in early life was associated with moderate‐to‐severe liver steatosis . The results of other famine studies were consistent with ours . There is also compelling evidence indicating that people who were stunted during infancy and childhood or who had low birth weight but subsequently had a continuous high‐fat diet (HFD) had higher susceptibility to fatty liver in later life .…”
Section: Introductionsupporting
confidence: 85%
“…Our previous study found that exposure to China's Great Famine of 1959–1962 in early life was associated with moderate‐to‐severe liver steatosis . The results of other famine studies were consistent with ours . There is also compelling evidence indicating that people who were stunted during infancy and childhood or who had low birth weight but subsequently had a continuous high‐fat diet (HFD) had higher susceptibility to fatty liver in later life .…”
Section: Introductionsupporting
confidence: 85%
“…Previous studies have shown that exposure to the Great Chinese Famine in early life increased the risks of obesity, hyperglycemia, type 2 diabetes, hypertension and fatty liver disease in adulthood, and also increased the risk of schizophrenia and death from stomach cancer in later life. [16][17][18][19][20][21][22] Our findings further suggested that exposure to the famine at the perinatal stage increased deaths from cardio-cerebrovascular disease (including stroke), cancer, diabetes, digestive disease and injury. Metabolic syndrome is an important risk factor of stroke, particularly among women and those with ischemic stroke.…”
Section: Discussionsupporting
confidence: 53%
“…For example, in the context of rodent models of nutritional modulation, a maternal energy-rich diet is associated with the development of NAFLD in offspring 153161 . In addition, as mentioned earlier, studies in humans have shown that fetal exposure to famine ‘mis-matched’ with a nutrient-rich adult environment 19, 162 is associated with the development of hepatic steatosis. Similarly, perinatal exposure to EDCs can result in adult susceptibility to development of NAFLD in rodent models (see Supplementary information S1 (table)), although only a limited number of these studies examined epigenetic alterations that could be responsible for NAFLD susceptibility.…”
Section: Liver Fat Metabolism and Edcsmentioning
confidence: 72%